Modulation of neurotrophic signaling pathways by polyphenols - Moosavi F; Hosseini R; Saso L; Firuzi O (Dove Medical Press, 2015)
Fatemeh Moosavi,1,2 Razieh Hosseini,1,2 Luciano Saso,3 Omidreza Firuzi1 1Medicinal and Natural Products Chemistry Research Center, Shiraz University of Medical Sciences, Shiraz, Iran; 2Department of Pharmacology, School of Veterinary Medicine, Shiraz University, Shiraz, Iran; 3Department of Physiology and Pharmacology “Vittorio Erspamer”, Sapienza University of Rome, Rome, Italy Abstract: Polyphenols are an important class of phytochemicals, and several lines of evidence have demonstrated their beneficial effects in the context of a number of pathologies including neurodegenerative disorders such as Alzheimer’s and Parkinson’s disease. In this report, we review the studies on the effects of polyphenols on neuronal survival, growth, proliferation and differentiation, and the signaling pathways involved in these neurotrophic actions. Several polyphenols including flavonoids such as baicalein, daidzein, luteolin, and nobiletin as well as nonflavonoid polyphenols such as auraptene, carnosic acid, curcuminoids, and hydroxycinnamic acid derivatives including caffeic acid phentyl ester enhance neuronal survival and promote neurite outgrowth in vitro, a hallmark of neuronal differentiation. Assessment of underlying mechanisms, especially in PC12 neuronal-like cells, reveals that direct agonistic effect on tropomyosin receptor kinase (Trk) receptors, the main receptors of neurotrophic factors including nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) explains the action of few polyphenols such as 7,8-dihydroxyflavone. However, several other polyphenolic compounds activate extracellular signal-regulated kinase (ERK) and phosphoinositide 3-kinase (PI3K)/Akt pathways. Increased expression of neurotrophic factors in vitro and in vivo is the mechanism of neurotrophic action of flavonoids such as scutellarin, daidzein, genistein, and fisetin, while compounds like apigenin and ferulic acid increase cyclic adenosine monophosphate response element-binding protein (CREB) phosphorylation. Finally, the antioxidant activity of polyphenols reflected in the activation of Nrf2 pathway and the consequent upregulation of detoxification enzymes such as heme oxygenase-1 as well as the contribution of these effects to the neurotrophic activity have also been discussed. In conclusion, a better understanding of the neurotrophic effects of polyphenols and the concomitant modulations of signaling pathways is useful for designing more effective agents for management of neurodegenerative diseases. Keywords: flavonoids, hydroxycinnamic acids, neuroprotective, neurodegeneration, Trk